2019
DOI: 10.1080/19396368.2019.1595217
|View full text |Cite
|
Sign up to set email alerts
|

Association of Luteinizing hormone and LH receptor gene polymorphism with susceptibility of Polycystic ovary syndrome

Abstract: Altered folliculogenesis and reproductive anomalies in polycystic ovary syndrome (PCOS) suggest that variations of genes involved in folliculogenesis might influence etiopathogenesis of this syndrome. The objective of this study was to assess the association of LHβ (rs1056917) and lutropin receptor (LHR) (rs61996318) polymorphism with polycystic ovarian syndrome and to interrelate the levels of luteinizing hormone (LH) with severity of clinical manifestations of PCOS. Three hundred women of reproductive age we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…They cited a report by Deswal et al ., in which luteinizing hormone and LH receptor (LHR) gene polymorphisms played an important role in determining LH and LH/FSH ratio. [ 2 ] The strong association of LHβ and LHR variations with high LH/FSH ratio was observed by them in their study along with the elevated levels of LH and LH/FSH ratio in majority of PCOS patients. In the present study, although we did not look for genetic polymorphisms in our patients which might be one of the causes for elevated levels, whatever may be the cause, the elevated levels did not impair the outcome of IVF/ICSI cycles in PCOS women.…”
mentioning
confidence: 87%
“…They cited a report by Deswal et al ., in which luteinizing hormone and LH receptor (LHR) gene polymorphisms played an important role in determining LH and LH/FSH ratio. [ 2 ] The strong association of LHβ and LHR variations with high LH/FSH ratio was observed by them in their study along with the elevated levels of LH and LH/FSH ratio in majority of PCOS patients. In the present study, although we did not look for genetic polymorphisms in our patients which might be one of the causes for elevated levels, whatever may be the cause, the elevated levels did not impair the outcome of IVF/ICSI cycles in PCOS women.…”
mentioning
confidence: 87%
“…Polymorphisms of FSRH and LHR have been involved in women with PCOS: FSHR gene p. Thr307Ala or p. Asn680Ser are associated with an increased risk for PCOS, clomiphene resistance, but better response to rFSH (26); LH SNP (rs61996318) CA and AA genotype conferred a significant risk in the development of PCOS (OR 5.07, 95% CI [2.50-10.31] (27).…”
Section: Prediction Of the Ovarian Response To Fsh Stimulationmentioning
confidence: 99%
“…To date, numerous studies suggested that genetic polymorphisms contribute substantially to the development of PCOS; over 100 genes are candidates, which functioned mainly in steroid biosynthesis, steroid action, glucose metabolism, and lipid metabolism ( 2 7 ). Rising interests were drawn in abnormal function of female sex hormone and hormonal receptors of PCOS women, and the impact of the mutation of some critical genes in the hormone metabolism pathways such as androgen receptor (AR) ( 8 ), luteinizing hormone receptor (LHR) ( 9 ), and follicle-stimulating hormone receptor (FSHR) ( 10 ) has been investigated in some meta-analyses. It was found that they were associated with some characteristics of PCOS such as clinical and/or biochemical hyperandrogenism, ovulatory dysfunction, and polycystic ovaries.…”
Section: Introductionmentioning
confidence: 99%